Body Size, Dispersal Potential, Range Size and Habitat Fragmentation Are Linked to Extinction Risk of Freshwater Mussels - Garrett W. Hopper; Sean M. Keogh; Carla L. Atkinson; Traci P. DuBose; Jeffrey D. Lozier; John M. Pfeiffer; Irene Sánchez González (Journal of Biogeography, 2026)
Aim Trait‐based approaches are increasingly recognised as tools for understanding species' vulnerabilities to intensifying global change. For species with complex life histories that involve a parasitic life stage, a combination of traits associated with either the host or parasite could influence extinction risk. Location United States of America. Taxon Freshwater mussels are a highly threatened assemblage of bivalves with an obligate ectoparasitic larval stage requiring a host fish. Adult mussels are sedentary, with long‐distance dispersal dictated by the dispersal ability of the host fish during the parasitic larval life phase. Methods We integrate several open‐source spatial and trait datasets for freshwater mussels and host fishes to test hypotheses about the relationship between species‐level traits such as body size, area of occupancy (AOO), host fish dispersal, habitat fragmentation and mussel extinction risk. Results Imperilled mussels were smaller, had smaller areas of occupancy, used small‐bodied, dispersal‐limited host fishes and had higher densities of large dams in their AOO compared to non‐imperilled mussels. Conclusions Body size, along with AOO and dispersal potential, appears to have cascading effects on imperilment where decreases in these traits potentiate population fragmentation via large dams. Thus, in contrast to many other groups, freshwater mussel body size is inversely related to extinction risk, and small‐bodied mussels should be closely monitored to prevent future extinctions.